SERANGAN HAMA DEFOLIATOR PADA BIBIT TANAMAN KEHUTANAN - Sri Utami; Agus Ismanto (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2016)
One of the efforts to support the success of forest plantation development is the availability of quality seeds (free from pests and diseases and have the ability to grow good). Defoliator pests is one of the problems frequently encountered pest attack seedlings in the nursery. Defoliator pest attacks will result in the failure of seedlings. The study was conducted at Modern Nursery located in the Sukamoro Village, Banyuasin, South Sumatra Province from February to May 2013. The purpose of the study was to analize the pest which attacks some seedlings e.g. Jabon (Anthocephalus cadamba), kayu bawang (Dysoxylum molissimum) and tembesu (Fagraea fragans) respectively 1 month old. The results showed that Arthroschista hilaralis is defoliator pests that attack several seedlings. A. hilaralis pest attacks Jabon begin observation two week with the percentage and intensity of attack by 40% and 30,39% respectively. The pest attacks continue to rise to observations in fourth week with a severity of 100%. The percentage and intensity of pests on kayu bawang seedling 68,72% and 40,66% respectively. On the seedlings tembesu, percentages and intensity of pest attacks 5,83% and 3,88% respectively, which is found in the observation of the 4th week. This showed that A. hilaralis is one of the pests that have a preference to eat in addition to its main host plant Jabon. Therefore, the presence of pests defoliator A. hilaralis on a scale nurseries should be anticipated. Management required appropriate controls in preventing these pests so that forestry plant breeding activities are carried out within the framework of the provision of seeds for planting in a broader scale having success.